Capturing the Industrial Requirements of Set-Based Design for the CONGA Framework - Al-Ashaab, Ahmed; Golob, Matic; Noriega, Paula; Torriani, Filippo; Alvarez, Pedro; Beltran, Ana; Busachi, Alessandro; Ex-Ignotis, Lambert; Rigatti, Carlotta; Sharma, Sanjiv (Cranfield University, 2013)
The Configuration Optimisation of Next-Generation Aircraft (CONGA) is a proposed framework in a response to industrial need to enhance the aerospace capability in the UK. In order to successfully address this challenge, a need to develop a true multi-disciplinary Set-Based Design (SBD) capability that could deploy new technologies on novel configurations more quickly and with greater confidence was identified. This paper presents the first step towards the development of the SBD capabilities which is to elicit the industrial requirement of the SBD process for the key aerospace industrial partners involved in this CONGA approach.